Controllability of infinite-dimensional systems with delays in control - Klamka, Jerzy (Annales Mathematicae Silesianae, 1985)
This paper considers the various types of controllability of linear infinite-dimensional dynamical systems defined in a Banach space, with multiple time-varying delays in control. Necessary and sufficient conditions for approximate controllability, approximate relative controllability and approximate absolute controllability of these systems are obtained. Special cases of systems defined in a Hilbert space are also considered.